(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the very important conditions for developing age-appropriate pedagogical methods of health care and physical education, taking into account the laws of development of the child’s organism and the performance characteristics of its systems at various stages of ontogenesis . According to modern concepts, all functions are united and change in the close interaction of the organism and the environment. The flexible nature of the organism’s activity at different ages is determined by two main factors: the morphological and functional maturity of physiological systems and the compatibility of the influencing environmental factors with the organism’s functional capabilities.